Effect of Holding Time and Temperature to The Sintered Characteristic of Alloy Formed Through Warm Compaction Route - Mohd Shauqi Bin Ahmad Shauqi (2023)
Sintering is a way of powder metallurgy in which the solid parts are manufactured from or ceramic powder mixtures. Sintering involves consolidating loose or loosely linked powders with or without extra stress at high temperatures close to the melting temperature. A particulate material is transformed into a strong compact body during sintering. At the macroscopic level, a change in the mechanical properties can be observed (a material gains a certain mechanical strength), a change in geometry and volumetric value also were recorded which shows after the result was taken during physical properties analysis. This process also provides heat treatment and convert a particulate material into a solid compact body. As the advantages of this process which occurs in a ceramic furnace is to enhance the bonding strength between particles inside the green product formed through the warm compaction route. Sintering takes place after the powder compaction process. The powder involved was prepared by mixing it and blended using a powder rotating mixer with a speed of 30 rpm and duration of 30 minutes. Moving to the sintering process, three parameters have been set for two manipulative variables involving holding time and the sintering temperature. Three different elevated temperature, i.e., 800°C, 900°C and 1000°C. The holding time was different with increment which at 30 min, 60 min and 90 min. After the sintering process finished on all samples, characterization was done next. Then, results exposed that sample sintered at temperature 1000°C with time 90 min have acquired the best bending strength but average electrical resistivity. Meanwhile, sample sintered at 900°C for 90 min got the best conductance properties but have average bending strength.